BONUS DEMOGRAFI PELUANG DAN TANTANGAN BAGI INDONESIA - Nur Falikhah (UIN Antasari Banjarmasin, 2017)
Indonesia gets demographic bonus in 2015-2035. Demographic bonus is when the number of productive population of the age of 15-64 years reaches about 70% or about 180 million people and the rest is about 30% or about 60 million people of unproductive age. The demographic bonus is like a double-edged sword. This demographic bonus becomes a profitable phenomenon on the one hand and on the other hand can be disastrous for a country. Beneficial and potential if a country is able to prepare its young generation with a quality generation and vice versa would be disastrous if the state is unable to prepare its human resources. High quality human resources both in terms of education, health, skills so as to compete in the world of work. This phenomenon is of course interesting to be studied further, especially how the opportunities and challenges for diversity in Indonesia.